KOMBINASI EKSTRAK DAUN KEMANGI DENGAN DAUN PEPAYA SEBAGAI INSEKTISIDA KUTU PINJAL - Setyo Dwi Santoso; Maulia Yunia Aisyah; Siti Nur Husnul Yusmiati; Dheasy Herawati (Jurnal SainHealth, 2022)
Cats that roam free and are not cared for are very susceptible to disease and do not rule out the possibility of being contagious to humans. Fleas as parasites that host cats can also interfere with human life directly or indirectly. Wrong a form of protection against flea attacks by using vegetable insecticides. This study aimed to determine the effect caused by the combination of basil leaves with papaya leaves against lice fleas on cats. This research is experimental research by macerating the basil leaves with the papaya leaves to take the extract. The extract formed was made in several concentrations of 30%, 40%, and 50% with the addition of aquadest as a diluent. Then the extract results were tested for their ability to affect fleas by spraying a sprayer. The results showed that. Basil leaves with papaya leaves are effective for controlling fleas. The combination of basil and papaya leaves can be used as a vegetable insecticide for fleas on the cat. Keywords: basil, papaya, insecticide, the flea